The Concepts of Karl Marx about Labor – Intransitive and Contemporary - Syarova, Elka (Research Papers, 2019)
One of the greatest minds of his time – Karl Marx, who is also one of the most controversial critics of the capitalism bequeaths an impressive scientific heritage. Two hundred years after his birth his works are still being an object of interest and various discussions, which is another inference that the topics he has aroused still nourish scientific reflections.The objective of this article is to examine some of K. Marx’s concepts about the labor and to discuss whether they are relevant in our present times. Based on their interpretation and critical analysis the article provides proofs of existence of some similarities between Marx’s concepts of Labor and Labor process and the modern perspective on these topics. They are also systemized some of the specific points in Marx’s Labor theory, as well as his standpoint about the compensation theory after the introduction of the machines. It has been drawn a comparison between his ideas and contemporary ones regarding the threat some jobs to become obsolete as a result of the introduction of robotized production and artificial intelligence.The summery and the inferences show that, despite of the time distance, some elements of Marx’s theories are not transitional and are still relevant even nowadays.